Efeitos da pandemia de COVID-19 na saúde dos trabalhadores de hospitais universitários - Vieira, Suelen Debora Fontana (Universidade Federal de São Carlos, 2023)
The Covid-19 pandemic has brought significant changes in the professional and personal life of hospitals workers, especially those who perform direct assistance to the population. Many workers were physically and emotionally exhausted, which contributes to the absenteeism due to several factors besides the contact with the Covid-19 virus. These workers can experience physical and mental overload and acquiring diseases by their own work environment in which they are inserted, facing daily exhausting situations such as dealing with death, suffering and pain. In periods of pandemic, these situations get worse by increased demand in hospitals and lack of structure to meet all the patients. As literature shows, sanitary outbreaks and pandemics periods are cyclic. In this context, it is relevant to have knowledge about the physical and mental health of these workers and the profile of absenteeism of this population. The aim of this study was to evaluate the data of absenteeism considering the care and administrative sectors of university hospitals in Brazil between 2018 and 2022, and to evaluate, in a sample of subjects of this population, the occupational fatigue, the work engagement, the symptoms of the Burnout syndrome and the musculoskeletal symptoms, to understand the effects of Covid-19 pandemic on the health of these workers. The survey was conducted in two stages, with workers from both the care and administrative sectors of university hospitals in Brazil (allocated by region), who were active in combating COVID-19 pandemic for at least 6 months. In the first stage, an analysis of the monthly mean of absenteeism by region, between 2018 and 2022 was performed. In addition, the classification of the absences according to the International Disease Classification System - 10th review, was presented. In the second stage, a survey was conducted through online and printed questionnaires, using the following instruments: a sociodemographic questionnaire, the Need for Recovery Scale, the Maslach Burnout Inventory-Human Services Survey (MBI-HSS), the Utrecht Work Engagement scale (UWES) and the Nordic Musculoskeletal Questionnaire (NMQ). The results of the first stage of the research showed that in 2020 and 2021 there was an increase in the absenteeism and in the monthly mean of absences per worker and hospital in all regions of Brazil. The most frequent health problems corresponded to infectious and parasitic diseases and respiratory diseases. In the second stage, the results of the questionnaires showed that 65.35% of workers had a high need for recovery. In addition, 31.37% had symptoms of the Burnout syndrome. Considering the engagement at work, 44.44% had a medium classification and a low percentage of the evaluated workers had engagement classified as “high” and “very high”. Considering the musculoskeletal symptoms, for the administrative sector the most affected region was the neck and for the care sector, the most affected region was the low back. In addition, the results show that musculoskeletal symptoms have developed or worsened for most workers. The results showed that in the period of the Covid-19 pandemic, both the physical and mental health of university hospitals workers presented quite negative aspects, evidenced by the alarming percentage of workers with fatigue, musculoskeletal symptoms, symptoms of burnout syndrome and the low percentage of workers with high engagement at work. These findings can guide the elaboration of prevention and treatment strategies focused on this population, especially when considering challenging contexts, such as pandemic periods. In addition, new studies seeking to evaluate the physical and mental health of these workers in the long term are still necessary.
Effects of the COVID-19 pandemic on the health of university hospital workers
Keywords: COVID-19; Ergonomics; Works health; Ergonomia; Saúde do trabalhador; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL